KEHARMONISAN KELUARGA PENGAMEN JALANAN - Silvie Mil; Shafira Fusta Ramadhani; Emiliya Alkhansa; Rimta Ravitaloka Simatupang; Khazaini Tanaffasa Juana; Yuni Dwi Hatati; Khansa Muthia Adila (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Harmonious families are shown through harmonious, happy, affectionate attitudes and less conflict. This study aims to find out how the harmony of the busker family, their relationships and factors that affect their harmonious. The research was conducted using a qualitative approach. Data collection was carried out using interviews, observations and documentations. Data analysis uses qualitative descriptive analysis where data was compiled, processed and analyzed to provide an overview of the harmony of busker families. The results of study stated that the busker family has harmonious family. Influencing factors were 1) Honesty, open communication, and full understanding among family members; 2) accepting dan respecting family members’ differences; 3) Spending sometimes with family to build proximity among family members; 4) Nondisruptive conflict resolution.